2009
DOI: 10.1002/pmic.200800738
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of proteins interacting with SIRT1 and SIRT3: implications in the anti‐aging and metabolic effects of sirtuins

Abstract: Sirtuins are a family of NAD(+)-dependent protein deacetylases that regulate cellular functions through deacetylation of a wide range of protein targets. Overexpression of Sir2, the first gene discovered in this family, is able to extend the life span in various organisms. The anti-aging effects of human homologues of sirtuins, SIRT1-7, have also been suggested by animal and human association studies. However, the precise mechanisms whereby sirtuins exert their anti-aging effects remain elusive. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 72 publications
2
86
0
Order By: Relevance
“…More recent studies have shown that SIRT3 deacetylates the succinate dehydrogenase flavoprotein subunit and increases complex II activity (Cimen et al, 2010). SIRT3 was also shown to directly bind and possibly deacetylate ATP5a (Law et al, 2009), a subunit of complex V. This evidence further supports a role for SIRT3 in regulating energy metabolism, which could provide beneficial effects during ischemic episodes.…”
Section: Roles Of Mitochondrial Sirtuins In Mitochondrial Metabolismsupporting
confidence: 51%
“…More recent studies have shown that SIRT3 deacetylates the succinate dehydrogenase flavoprotein subunit and increases complex II activity (Cimen et al, 2010). SIRT3 was also shown to directly bind and possibly deacetylate ATP5a (Law et al, 2009), a subunit of complex V. This evidence further supports a role for SIRT3 in regulating energy metabolism, which could provide beneficial effects during ischemic episodes.…”
Section: Roles Of Mitochondrial Sirtuins In Mitochondrial Metabolismsupporting
confidence: 51%
“…Specifically, deacetylation regulates the activity of IDH (Schlicker et al, 2008), cytochrome c reductase (Ahn et al, 2008) and MDH ; three enzymes we identified in M. trossulus together with sirtuin 5. A recent study identified a number of proteins interacting with sirtuins (Law et al, 2009), including several Hsp70s and MAPK/Erk; again, these are proteins we found responding to acute heat stress in Mytilus. In addition, a reduction in MAPK/Erk is generally associated with reduced cell survival (Nadeau and Landry, 2007), an observation consistent with our results in M. trossulus and the reduction of the sirtuin 5 isoform (Figs3 and 10).…”
Section: Hypotheses Integrating the Observed Heat-stress-induced Chanmentioning
confidence: 96%
“…In addition, vectors encoding glutathione S-transferase (GST)-tagged SIRT1 mutants (GST-hSIRT1-S47A and GSThSIRT1-S47D) were constructed by use of the template plasmid GST-hSIRT1-WT. 30 All mutations were confirmed by DNA sequencing.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%